2019
DOI: 10.1007/s11119-019-09696-0
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of management zones with spatial data fusion and belief theory

Abstract: Precision agriculture, as part of modern agriculture, thrives on an enormously growing amount of information and data for processing and application. The spatial data used for yield forecasting or the delimitation of management zones are very diverse, often of different quality and in different units to each other. For various reasons, approaches to combining geodata are complex, but necessary if all relevant information is to be taken into account. Data fusion with belief structures offers the possibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…For green vegetation, the reflection in the red region is always less than in the near infrared, due to the absorption of light by chlorophyll, so the NDVI values for vegetation cannot be less than 0. To obtain the NDVI map, an index was calculated for each pixel of the Landsat 5 space image with a spatial resolution of 30 meters in the red and near infrared spectral zones [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…For green vegetation, the reflection in the red region is always less than in the near infrared, due to the absorption of light by chlorophyll, so the NDVI values for vegetation cannot be less than 0. To obtain the NDVI map, an index was calculated for each pixel of the Landsat 5 space image with a spatial resolution of 30 meters in the red and near infrared spectral zones [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…For the correlation analysis, 15 indices that are frequently used both in research and in precision farming practice, were selected (Lilienthal, 2014;Siegmann et al, 2012). In accordance with the studies of Georgi et al (2017) and Vallentin et al (2019), which are based on the same satellite and yield data sets, the choice of indices was narrowed down to yield-relevant spectral indices (Table 3). The indices were calculated from appropriate spectral bands of the different sensors, which are varying in number and wavelength range.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation result is given as Spearman Correlation Coefficient r (Daniel, 1990), also called "Spearman's Rho", and always refers to the correlation between the yield data and the respective data source to be analyzed.. Earlier studies (Georgi et al, 2017;Vallentin et al, 2019) showed a monotonous but non-linear correlation between satellite data and yield data, which would rule out correlation methods based on linear correlation assumptions. One reason for the non-linearity is the saturation of vegetation indices (Esau et al, 2016;Haboudane, 2004), which in high ranges do not correlate as strongly with the yield as in the lower and middle ranges.…”
Section: Methodsmentioning
confidence: 99%
“…Multi sensor Data Fusion Environment: Sensors with Different agriculture variants have been used to provide information that are capable in monitoring and optimizing growth level of plants, land water stage, humidity stage, soil category and temperature point of the agriculture ground as per the varying environmental factors [19] .These sensors inspect by penetrating the soil and records resistive forces before sending them to the central node for further data integration and data fusion [12].…”
Section: Deployment Of Agricultural Sensorsmentioning
confidence: 99%